1983
DOI: 10.1104/pp.73.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Conjugation of Gibberellins In Situ in Maize

Abstract: Gibberellins [HJGA4 (133 Curies per millimole) and I3HIGAn (2.36 Curies per millimole) were injected into the shanks of maize (Zea mays L.) cobs during rapid grain filling and mature seeds were subsequently harvested. Extracts of mature, dry seeds from 1980 feeds yielded only 20 to 30% of the 3H radioactivity in acidic, ethyl acetate-soluble form, and this was principally associated with the precursor, with lesser amounts of the major metabolite, [3HIGA, (putative to re-examine the possibility that revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…This graded response to increasing levels of GA3 suggests that gibberellin was limiting in kernels which have not been dried. Rood et al (21) found that mature seeds contain predominantly glucosyl conjugates 6 HAI 010…”
Section: Discussionmentioning
confidence: 99%
“…This graded response to increasing levels of GA3 suggests that gibberellin was limiting in kernels which have not been dried. Rood et al (21) found that mature seeds contain predominantly glucosyl conjugates 6 HAI 010…”
Section: Discussionmentioning
confidence: 99%
“…SiO, partition chromatography was performed on each extract to further separate free GAs from GA conjugates (adapted from Rood et al, 1983). Briefly, the samples were dissolved in 0.5 mL of methano1:ethyl acetate:H,O (50:50:1, v/v) and placed at the top of a SiO, column (1 g; 20% H,O by weight) which had been slurried and packed with formic acid-saturated hexane:ethyl acetate (95:5, v/v).…”
Section: Chromatographymentioning
confidence: 99%
“…Water in the EtOAc-soluble extract was removed by freezing and filtration of ice, and the EtOAc was taken to dryness in vacuo at 35°C. After freeze-drying, the extract residue was dissolved in MeOH:EtOAc (1:1) and loaded onto glass-fiber filter paper discs prior to stepwiseelution SiO2 partition column chromatography (3,21). The resulting 26 fractions were bioassayed at 1/200 and 1/400 dilutions using a modified (19) Tan-ginbozu dwarf rice microdrop assay (13).…”
Section: Analysis Of Gibberellin-like Substancesmentioning
confidence: 99%